Double teeth in primary dentition: Report of two clinical cases - Guimarães Cabral, Luiz Antonio; Firoozmand, Leily Macedo [UNESP]; Dias Almeida, Janete (My University, 2008)
Odontogenic anomalies can occur as a result of conjoining or twinning defects. These include fusion, gemination and concrescence. This article presents two case reports of double teeth. In the first case reported, a 4 -year-old white boy presented primary double teeth associated to the absence of the right permanent mandibular lateral incisor. In the second case, a 5-year-old white girl had a family history of anomaly in primary dentition. The girl and her mother presented double teeth in the primary dentition. Her mother showed hypodontia in the permanent dentition. Extra and intra oral clinical examination was made in both cases. Radiographic analyses showed the involvement of the permanent tooth. Authors conclude that double teeth in primary dentition have to be carefully analysed as they may be associated with anomalies in the permanent dentition. Correct diagnosis of the condition implicates in a better prognosis for the patient. © Medicina Oral S. L. C.I.F.
Keywords: Dental pathology; Double teeth